Dampak Kemampuan Soft Skill, Keahlian Akuntansi, dan Literasi Digital Terhadap Kesiapan Kerja Mahasiswa Jurusan Akuntansi: Studi Pada Mahasiswa Akuntansi Perguruan Tinggi Negeri di Bandar Lampung - Nancy Geaninda Arziati; Endang Aslian; Irawan Irawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted with the aim of determining the influence of soft skills, accounting expertise, and digital literacy on the job readiness of accounting students (a study on accounting students at State Universities in Bandar Lampung) both partially and simultaneously. The type of data used is primary data obtained through the distribution of questionnaires. The population in this study consists of accounting students from State Universities in Bandar Lampung, totaling 3,834 students. The sampling method in this study uses a non-probability sampling method, specifically the purposive sampling technique, and obtained a sample of 110 respondents. The data analysis method used is multiple linear regression analysis using the SPSS Ver.27 testing tool. The research results show that partially, soft skills, accounting expertise, and digital literacy have a positive impact on the job readiness of accounting students.